A systematic review on markers of functional overreaching in endurance athletes - Roete, A. J.; Elferink-Gemser, M. T.; Otter, R. T. A.; Stoter, I. K.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of this brief review was to present an overview of noninvasive markers in trained to professional endurance athletes that can reflect a state of functional overreaching.